PENGARUH STROKING MASSAGE DAN OLIVE OIL TERHADAP PENURUNAN SKALA PRURITUS UREMIK PADA PASIEN GAGAL GINJAL KRONIS YANG MENJALANI HEMODIALISA DI RSUD SULTAN IMANUDIN PANGKALAN BUN - Astriya, Oca; Fatmawati, Zuliya Indah; Sucipto, Ade (Jurnal Borneo Cendekia, 2024)
Background: Chronic renal failure is a decrease in kidney function to maintain metabolism and electrolytes. One of the treatments for chronic renal failure is hemodialysis, one of the complications after hemodialysis is uremic pruritus. Uremic pruritus is an uncomfortable sensation or itching in patients with chronic renal failure undergoing hemodialysis. Research method: The type of quantitative research with a quasi-experimental design of two groups pretest and posttest, the number of samples was 30 respondents with random sampling technique, the measuring instrument for the uremic pruritus scale used NRS. Results: A total of 30 respondents were divided into two intervention groups and a control group. Where the intervention group was given stroking massage and olive oil twice a week and the duration of the action was 7 minutes. While the control group was only given pharmacological therapy. From the results of data analysis using the Wilcoxon Test on the pre-test and post-test of the experimental group, it was found that the P value = 0.000 which means P value ? ? (0.05). While the results of the Wilcoxon Test in the control group found that the P value = 0.014 which means P value ? ? (0.05). The results of the Mann Whitney Test comparing the post-test of the experimental group and the control group showed that the P value = 0.009 then the P value ? ? (0.05). Conclusion: From the results of the study, it can be concluded that there is an effect of giving stroking massage and olive oil on reducing the scale of uremic pruritus in chronic kidney failure patients undergoing hemodialysis at Sultan Imanudin Hospital, Pangkalan Bun. Keywords: stroking massage, olive oil, uremic Pruritus, chronic kidney disease, hemodialysis